Adequacy of Fund Resources-Further Considerations. - International Monetary Fund. Finance Dept. (Washington, D.C. : International Monetary Fund, 2021)
This paper is part of the workplan on the 15th General Review of Quotas (15th Review). The paper provides a two-pillar framework for assessing the adequacy of Fund resources, building on the staff paper discussed by the Board in March 2016. The second pillar of the framework is qualitative in nature. The paper also provides information to support a discussion on the mix of Fund resources.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet